The Market Linkage - Fuchs, Victor E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
The Market Linkage Project (ML) for Special Education and the Basic Skills Validation and Marketing Program are two federally sponsored marketing projects developed under contract by LINC Resources, Inc., a professional marketing organization, for the U.S. Department of Education. LINC developed the marketing programs to provide the option for the commercial production, publication, and distribution of federally funded programs and products. The marketing programs represent a dissemination model in which government and industry work together and, as such, the LINC model can be identified as the commercial or business model of dissemination. The ML provides the following benefits: (1) The product developer benefits from the satisfaction of publication and national or international distribution; (2) The federal government (taxpayers) benefits by obtaining the largest and most effective marketing and distribution system available for educational products at no cost; and (3) The publishing industry benefits by having a supply of quality products made available to it. (RL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Federal Programs; Industry; Information Dissemination; Marketing; Models; Special Education; Department of Education -- Market Linkage Project; Reports, Descriptive